Fontidessus Miller and Spangler, a new genus of Bidessini from Venezuela (Coleoptera: Dytiscidae: Hydroporinae) with three new species - Miller, Kelly B.; Spangler, Paul J. (Zootaxa, 2008)
A new genus, Fontidessus n. gen., and three new species F. toboganensis n. sp., F. ornatus n. sp., and F. wheeleri n. sp., are described from Venezuela. The new genus is similar to Uvarus and Bidessodes but is distinguished from all other Bidessini (including these) by a combination of the following: 1) transverse occipital line absent, 2) basal pronotal striae present, 3) basal elytral stria absent, 4) elytral sutural stria faintly present in some specimens, 5) anterior clypeal margin unmodified, 6) elytron without longitudinal carinae, 7) epipleuron without transverse carina at humeral angle, 8) lateral lobes of aedeagus two-segmented, 9) habitus elongate, oval, with lateral pronotal and elytral margins nearly continuously and shallowly curved, and 10) metatrochanter extremely large relative to metafemur, approximately 0.6 × length of metafemur.